Pengembangan Kurikulum ISMUBA dalam Meningkatkan Kualitas Pendidikan Muhammadiyah - Mundofi, Ahmad Asron (Jurnal Studi Islam dan Kemuhammadiyahan (JASIKA), 2024)
The development of curricula is a critical aspect in creating quality education that is relevant to religious values. This study deals with the "Development of Curriculum al-Islam, Kemuhammadiyahan, and Language (ISMUBA)" as a manifestation of the characteristic of education in Muhammadiyah institutions. ISMUBA is not just an abbreviation, but a reflection of the commitment to formulate a curriculum that integrates Islamic values, religion, and language as a holistic unity. This approach creates a holistic and in-depth learning environment, encompassing an understanding of Islamic teachings, the spirit of Muhammadiyah, and the mastery of language as an effective means of communication. The curriculum is designed to build a strong character, good ethics, and language skills that support the development of learners in a global context. ISMUBA also emphasized the active involvement of learners in the development of language skills, both Arabic as the language of the Qur'an and as a means of daily communication. Thus, ISMUBA not only produces graduates who have academic intelligence, but also fosters religious attitudes, humility, and comprehensive language skills. This study details the pedagogical principles underlying ISMUBA, describes the process of curriculum development, as well as gives insight into its impact on character formation and student performance. It is hoped that the implementation of ISMUBA can be an inspiring model for other educational institutions that advance religious values and integrate with general education.